THE RELATIONSHIP BETWEEN BREASTFEEDING FREQUENCY AND THE MASTITIS OCCURRENCEÂ IN THE FIRST -Â SIX MONTHS IN BPM NY. KASIYANI, SST, M.Kes TROWULAN â MOJOKERTO - Kusmindarti, Indah; Hudaningsih, Ulfa (JURNAL KEPERAWATAN SEHAT, 2016)
The relationship is the process of feeding baby using mother breast milk. Mother breast milk containing all the vitamins and nutrients for baby needs. Most of mother problems in giving exclusive breast feeding is mastitis. Mastitis is caused by blocking occurrence in mother breast milk duct. The purpose of this research is to know the relationship between breastfeeding frequency and the mastitis in the first six months of a baby’s life. This research using analytic method and cross sectional approach. The population of this research is forty eight (48) respondents. The respondents choosen by using probability technic and consecutive sampling. The sample of this research is using free frequency variabel to the breastfeeding problems. The variabel tied to mastitis occurrence. The instrument using quetioner primary data and processed by editing, coding, scoring and tabulating. The analyse statistic test using chi – square test. The data is calculated using spss 20. The chi square test result shows that 28 respondent (58,3%) not optimally give exclusive breastfeeding to their baby , and 27 respondents (56,3%) faced mastitis occurrence. There is relationship between breastfeeding and the mastitis in BPM Ny. Kasiyani, SST,M.Kes Trowulan – Mojokerto . Based on chi-square statistic test with significant standart a =0,05 resulting x2 = 18,307 with p = 0,000 < a= 0,05 . So, p result = 0,000 <a = 0,05 this research purpose to give more information about mastitis. The writer advices to all respondents to be consistent hold breastfeeding program to avoid mastitis occurrence. Hopefully, this research also can be used for health training program such as posyandu especially for suckling mother.Keywords : suckling mother, breastfeeding, mastitis.